Gestão pública: o impacto do SEI na coordenação administrativa do INC - Moraes, Joeliton Vargas (Brasil, 2024)
With technological advancements, Public Administration has increasingly utilized electronic documents and processes as a strategic condition to achieve its objectives, playing a crucial role in society. This Graduation Thesis (TCC) aims to analyze the impact of the implementation of the Electronic Information System (SEI) on the administrative processes of the Administrative Coordination (CA) of the Institute of Nature and Culture (INC) of the Federal University of Amazonas (UFAM). The research is qualitative, using a descriptive method, with observation and interview techniques. The research instrument adopted was a semi-structured script. Conducted in the Administrative Coordination of the INC, the research had the academic community as its universe, and the sample consisted of the Administrative Coordination staff, one professor, and one student. Using a deductive approach, both primary and secondary sources were employed, integrating field and bibliographic research. The results obtained show that the implementation of SEI brought significant improvements to administrative processes, such as the reduction of paper usage, increased efficiency in process handling, centralization and organization of information, as well as greater security and traceability. These changes contribute to more efficient and transparent management, aligning with the principles of the new public management. Before SEI, the dependence on physical documents posed challenges such as slow processing, high paper consumption, and risks of loss. With the introduction of SEI, a 90% reduction in paper usage was observed, along with significant improvements in the agility and security of processes, information centralization, and better task management. The research also identifies limitations and suggests areas for future studies, highlighting the importance of digitalization in modern public administration.